PENINGKATAN PROFESINALISME GURU MELALUI PERAN KEPALA SEKOLAH SEBAGAI SUPERVISOR - Sumarno Sumarno; Muh. Husein Muttaqien (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2019)
Teachers become professionals in maintaining the quality of education depending on the principal in carrying out their functions as supervisors. The principal in improving the professionalism of teachers is to provide motivation and a sense of security in working, establishing professional working relationships, self actualisation and self development teachers, exchanging opinions or (sharing), cooperation in prevention and improvement and improvement of quality of learning. The obstacles faced by the principal as a supervisor in developing the professionalism of teachers are the facilities and infrastructures that have not been fulfilled as a whole, there is a sense of the senior teacher and the school's financial condition is still lacking. Efforts undertaken by the principal as a supervisor in overcoming various obstacles in developing the professionalism of teachers, among others, complement the facilities and infrastructure, be flexible and communicate well with the teachers and staff and develop the source of funds.